PENGARUH AUDIT TENURE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2018-2020 - Arizah, Ainun; Sasmita, Sasmita; Khalid, Ansyarif (Indonesian Journal of Research in Economy, 2022)
The purpose of this study is a quantitative type of research with the aim of knowing the effect od audite tenure on earnings management in manufacturing companies in the basic and cheminal industri sectors listed on the Indonesia Stock Exchange in 2018-2020. In this study, the data sources used in data collection include secondary data. The research variable used is Audit Tenure as the independent variable while Earnings Management as the dependent variable. The population in this study are manufacturing companies in the Basic and Chemical Industri Sector Listed on the Indonesia Stock Exchange in 2018-2020 while the samples used in this study were 39 manufacturing companies in the basic and cheminal industry sectors that met the sample criteria during the study period. The sampling technique in this study used purposive sampling. Analysis of the data used is simple regression analysis. The result of the study indicate that audit tenure has no effect on earnings management.